تاثيرات الصور الرقمية لمجازر الصهاينة في حرب غزة من خلال تطبيق التيك توك على الطلبة الجامعيين - مروة بونيف; د/ عبدالقادر النوعي (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة دراستنا بعنوان تأثيرات الصور الرقمية لمجازر الصهاينة في حرب غزة من خلال تطبيق التيك توك على الطلبة الجامعيين (دراسة ميدانية على طلبة جامعة عمار ثليجي بالأغواط)،انطلقت من التساؤلالتالي: مامدى تأثير الصور الرقمية لمجازر الحرب على غزة على الطلبة الجامعيين عبر تيك توك؟ ومنه نطرح عدة تساؤلات فرعية كالتالي: 1- ما مدى تأثير الصور الرقمية لمجازر الحرب على غزة على الاتجاهات السياسية للطلبة الجامعيين عبر تيك توك؟ 2- ما مدى تأثير الصور الرقمية لمجازر الحرب على غزة على الاتجاهات الدينية للطلبة الجامعيين عبر تيك توك؟ وتهدفالدراسة بشكل عام الى التعرفعلى تأثيرات الصور الرقمية لمجازر الصهاينة في حرب غزة من خلال تطبيق التيك توك على الطلبة الجامعيين، كما اهتمتبفهم التأثيرالعميقلوسائلالتواصلالاجتماعي،وخاصةتطبيقتيكتوك،علىإدراكالطلابالجامعيينللأحداثالجاريةفيغزة، كما تم الاعتماد على المنهج الوصفي وأداة جمع البيانات التي تمثلت في استمارة الاستبيان،حيث تكون مجتمع البحث من طلبة جامعيين من جامعة عمار ثليجي بالأغواط والبالغ عددهم 150طالبا وطالبة، ومن خلال عرض وتحليل ومناقشة نتائج الدراسة توصلنا الى النتائج التالية: أكثر طلبة جامعة الاغواط يشاهدون صور ومقاطع فيديو عن مجازر الصهاينة في غزة على تطبيق تيك توك. 1. مشاهدة الطلبة لصور الرقمية حول مجازر الصهاينة في غزة عبر التيك توك غيرت كثيرا من نظرتهم السياسية للحرب على غزة كما أكد وجهات نظرهم السابقة عن تلك المجاوز. 2. نسبة كبيرة من طلبة جامعة الاغواط يرون أن الصورالرقمية عبر التيك توك عن القضية الفلسطينية غيرت من نظرتهم للعلاقة بين الدين والسياسة في الشرق الأوسط من خلال عدة نقاط كما اجابوا أهمها عدم المساندة لقضية الدين التي تمارسها إسرائيل في فلسطين حيث ظهر عدون إسرائيل للدين الإسلامي عامة. 3. الصور الرقمية للحرب على غزة عبر التيك توك عززت من رغبت الطلبة في المشاركة في أنشطة دينية داعمة للقضية الفلسطينية من خلال نشر والدعاء وتنظيم الحملات الدينة المساعدة والداعمة للقضية الفلسطينية. الكلمات المفتاحية: التأثير -الصورة الرقمية-مجازر الصهاينة في حرب غزةتطبيق التيك توك-الطلبةالجامعيين Summary : Our study, entitled The Effects of Digital Images of Zionist Massacres in the Gaza War through the Application of Tik Tok on University Students (A Field Study on the Students of Ammar Theliji University in Laghouat), was launched from the following question: What is the extent of the impact of digital images of massacres of the war in Gaza on university students via Tik Tok? From this, we raise several sub-questions as follows: 1. To what extent do digital images of war massacres in Gaza affect the political attitudes of university students via TikTok? 2. To what extent do digital images of war massacres in Gaza affect the religious attitudes of university students via TikTok? The study aims in general to identify the effects of digital images of Zionist massacres in the Gaza War through the application of Tik Tok to university students. It was also concerned with understanding the profound impact of social media, especially the Tik Tok application, on university students’ perception of the current events in Gaza. It was also adopted Based on the descriptive approach and the data collection tool, which was represented by the questionnaire form, the research community consisted of university students from Ammar Theliji University in Laghouat, numbering 150 male and female students, and through presenting, analyzing and discussing the results of the study, we reached the following results: Most Laghouat University students watch pictures and videos of the Zionist massacres in Gaza on the TikTok application. 1. The students’ viewing of digital images of the Zionist massacres in Gaza via Tik Tok greatly changed their political view of the war on Gaza and also confirmed their previous views on those transgressions. 2. A large percentage of students at the University of Laghouat believe that digital images on TikTok about the Palestinian issue have changed their view of the relationship between religion and politics in the Middle East through several points, as they answered, the most important of which is the lack of support for the issue of religion practiced by Israel in Palestine, where Israel’s hostility to the Islamic religion appeared. General. 3. Digital images of the war on Gaza via Tik Tok strengthened students’ desire to participate in religious activities in support of the Palestinian cause by publishing, praying, and organizing religious campaigns that help and support the Palestinian cause. Keywords: influence - digital image - Zionist massacres in the Gaza war - TikTok application - university students
دراسة ميدانية على طلبة جامعة عمار ثليجي بالاغواط